Magnesium supplementation reduces inflammation in rats with induced chronic kidney disease. (18th April 2021) - López‐Baltanás, Rodrigo; Encarnación Rodríguez‐Ortiz, Maria; Canalejo, Antonio; Díaz‐Tocados, Juan M.; Herencia, Carmen; Leiva‐Cepas, Fernando; Torres‐Peña, José D.; Ortíz‐Morales, Ana; Muñoz‐Castañeda, Juan Rafael; Rodríguez, Mariano; Almadén, Yolanda
Abstract: Background: Inflammation is a common feature in chronic kidney disease (CKD) that appears specifically associated with cardiovascular derangements in CKD patients. Observational studies have revealed a link between low Mg levels and inflammation. In this study, we hypothesize that Mg might have a modulatory effect on the inflammation induced under the uraemic milieu. Methods: In vivo studies were performed in a 5/6 nephrectomized rat model of CKD. Furthermore, a possible direct effect of Mg was addressed through in vitro studies with vascular smooth muscle cells (VSMCs). Results: Uraemic rats fed a normal (0.1%) Mg diet showed a systemic inflammatory response evidenced by the elevation in plasma of the pro‐inflammatory cytokines TNF‐α, IL‐1β and IL‐6, and GPx activity, a marker of oxidative stress. Importantly, an increased expression of these cytokines in the aortic tissue was also observed. In contrast, a dietary Mg supplementation (0.6%) greatly prevented the oxidative stress and the pro‐inflammatory response. In vitro, in VSMCs cultured in a pro‐inflammatory high phosphate medium, incubation with Mg 1.6 mM inhibited the increase in the production of ROS, the rise in the expression of TNF‐α, IL‐1β, IL‐6 and IL‐8 and the activation of NF‐κB signalling that was observed in cells incubated with a normal (0.8 mM) Mg. Conclusion: Mg supplementation reduced inflammation associated with CKD, exerting a direct effect on vascular cells. These findings support a possible beneficial effect of Mg supplementation along the clinical management of CKD patients.